Physical Activity in Mental Health Disorders – Therapeutic Potential and Mechnisms - Maria Wachowska; Paweł Maciej Rycąbel; Mateusz Romaniuk; Marek Jarosław Molenda; Mateusz Paniak; Wojciech Jan Sowiński; Oliwia; Marta Szymura; Agnieszka Ewelina Wojciechowska; Michał Brunon Krawczyk (Quality in Sport)
Introduction and Purpose: Mental health disorders are a global public health challenge, with rising emergency visits, especially among youth. Physical activity has gained recognition as an effective intervention for some mental disorders. PA positively affects mental health by enhancing neuroplasticity, neurotransmitter regulation, and reducing inflammation. Aerobic and resistance exercises, as well as yoga, are effective in alleviating depressive symptoms, anxiety, and PTSD, improving ADHD-related cognitive functions, and decreasing substance cravings. This study aims to analyze the influence of physical activity on mental disorders.